A propósito del artículo “La prevención cuaternaria en la atención médica ambulatoria y hospitalaria” - Machin Rodriguez, Vivian Teresa (Mediciego, 2019)
As its author says, quaternary prevention has been discussed in different Ibero-American events and summits on family and community medicine, by the Pan American Health Organization and the World Health Organization, government and academic institutions, local governments, and civil societies.